INTERNALISASI LITERASI ENTREPRENEURSHIP DALAM MEMBANGUN KARAKTER KEMANDIRIAN EKONOMI ANAK USIA SEKOLAH DASAR - lia Ernawati (STKIP Subang, 2025)
The rapid development of technology and changing patterns of social interaction demand the emergence of a generation that is independent, creative, and highly adaptable. Elementary education, as a foundational phase, can play a strategic role in shaping independent character through the application of entrepreneurial literacy. This article comprehensively examines the concept of entrepreneurial literacy, its relevance in elementary education, and its contribution to the development of children's sense of independence. Through a literature review, this paper concludes that entrepreneurial literacy not only enhances creativity and problem-solving but also instills the values ​​of hard work, responsibility, and self-confidence. The integration of entrepreneurial literacy through project-based learning, a supportive school environment, and parental involvement has proven effective in developing children's independence in elementary school.